Passenger Occupancy Phenomena of Trans Jakarta due to COVID-19: A Case Corridor X (2019-2021) - Asadulhaq, Saifan Pabelano; Rifai, Andri Irfan; Handayani, Susanty (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
Bus Rapid Transit (BRT) in modern times has become a prevalent issue in various parts of the world. The reasons are passenger appeal and expandability, high performance, and quality, as well as its buildability quickly, step-by-step, and ergonomics. With all this flexibility, BRT can provide high-quality transit performance over a wide range of geographic areas outside of dedicated lanes. This paper aims to find out the passenger occupancy phenomena of BRT in the main corridors in Jakarta. The hope is that BRT operators and regulators can optimally provide services for users after knowing the growing trend. The method used is to know the trend based on the graph of the number of BRT users in 2019-2020. The study results concluded trend of annual passengers has decreased by more than 50%, which is thought to be due to the COVID-19 Pandemic. While the monthly passenger trend will increase by 14% in November and December, this is a due accumulation of activities at the end of the year. Furthermore, the daily passenger trend is dominated by weekdays on Mondays, with the number of passengers 28% above the daily average